Efektivitas Sistem Informasi Akuntansi Pada UMKM Kota Pematangsiantar - Rotua Juliana S; Maya Sari Saragih; Muhammad Ridha Habibi Z; Taufik Hidayat; Sofyan Hidayat; Nisha Marina (Jurnal Ilmu Ekonomi dan Bisnis, 2024)
In research regarding "The Influence of User Competence, Task Complexity, and Sophistication of Information Technology on the Effectiveness of Accounting Information Systems in MSMEs in Pematangsiantar City," the results of data analysis showed interesting findings. First, related to User Competence, the p-value is 0.356, which indicates that there is no significant influence on the Effectiveness of the Accounting Information System, which indicates theacceptance of the null hypothesis (H0), meaning that User Competence does not have a significant influence on the Effectiveness of the Accounting Information System. Then, related to Task Complexity, the p-value is 0.111, indicating that there is no significant influence on the Effectiveness of the Accounting Information System, which alsosupports the acceptance of the null hypothesis (H0), meaning that Task Complexity does not significantly influence the Effectiveness of the Accounting Information System. However, interesting findings emerged related to the Sophistication of Information Technology, where the p-value was 0.004, indicating a significant influence on the Effectiveness of the Accounting Information System. This rejects the null hypothesis (H0) and shows that Information Technology Sophistication has a significant influence on the Effectiveness of Accounting Information Systems in Pematangsiantar City MSMEs. These findings give the impression that increasing Information Technology Sophistication can positively influence the Effectiveness of Accounting Information Systems in MSMEs, while the UserCompetence and Task Complexity factors do not have a significant influence.